Divorce and household balance in Indonesia - Hadi, Dudi Abdul; Agustina, Ingrid Larasati; Nuryaman, Nuryaman (Technium Business and Management, 2024)
This research aims to gain knowledge about the causal relationship between divorce and household balance sheets in Indonesia. This research is descriptive using a simple linear regression analysis tool. The balance of households in Indonesia is currently experiencing a quite large increase. The household balance sheet is comprehensive information regarding the activities of all households in Indonesia. The cause of changes in household balance sheets can be described as a result of divorce, which is currently also experiencing an increase in the number of cases. Divorce has a contribution to household balance sheets in Indonesia, so, practically, information is needed on what economic activities can occur as a result of divorce, involving religious courts to the government and theoretically in household and financial accounting. The results of the research illustrate the causality relationship between divorce and household balance sheets in Indonesia, which means household accounting is affected by divorce on a large scale, namely the state.